Acetylated tau, a novel pathological signature in Alzheimer's disease and other tauopathies - Irwin, David J. (Oxford University Press, 2012)
The microtubule-binding protein, tau, is the major component of neurofibrillary inclusions characteristic of Alzheimer's disease and related neurodegenerative tauopathies. When tau fibrillizes, it undergoes abnormal post-translational modifications resulting in decreased solubility and altered microtubule-stabilizing properties. Recently, we reported that the abnormal acetylation of tau at lysine residue 280 is a novel, pathological post-translational modification. Here, we performed detailed immunohistochemistry to further examine acetylated-tau expression in Alzheimer's disease and other major tauopathies. Immunohistochemistry using a polyclonal antibody specific for acetylated-tau at lysine 280 was conducted on 30 post-mortem central nervous system regions from patients with Alzheimer's disease (10 patients), corticobasal degeneration (5 patients), and progressive supranuclear palsy (5 patients). Acetylated-tau pathology was compared with the sequential emergence of other tau modifications in the Alzheimer's disease hippocampus using monoclonal antibodies to multiple well-characterized tau epitopes. All cases studied showed significant acetylated-tau pathology in a distribution pattern similar to hyperphosphorylated-tau. Acetylated-tau pathology was largely in intracellular, thioflavin-S-positive tau inclusions in Alzheimer's disease, and also thioflavin-S-negative pathology in corticobasal degeneration and progressive supranuclear palsy. Acetylated-tau was present throughout all stages of Alzheimer's disease pathology, but was more prominently associated with pathological tau epitopes in moderate to severe-stage cases. These temporal and morphological immunohistochemical features suggest acetylation of tau at this epitope is preceded by early modifications, including phosphorylation, and followed by later truncation events and cell death in Alzheimer's disease. Acetylation of tau at lysine 280 is a pathological modification that may contribute to tau-mediated neurodegeneration by both augmenting losses of normal tau properties (reduced solubility and microtubule assembly) as well as toxic gains of function (increased tau fibrillization). Thus, inhibiting tau acetylation could be a disease-modifying target for drug discovery target in tauopathies.